INNOVATION IN REAL ESTATE SALES STRATEGIES: A STUDY ON THE ADOPTION OF DIGITAL TECHNOLOGIES AND CRM - Cristina Constantino da Costa Silva, Amanda (Journal of Interdisciplinary Debates, 2025)
The real estate sector is undergoing an accelerated digital transformation, redefining sales strategies and customer relationships. This paper investigates how high-performance real estate brokerages are using digital technologies, with a focus on Customer Relationship Management (CRM) systems, to optimize lead conversion and customer loyalty. Through a systematic literature review and analysis of secondary market data, the study explores the benefits, challenges, and performance metrics associated with technology adoption. The results indicate that while CRM implementation can generate a return on investment (ROI) exceeding 200% and increase productivity by over 30%, adoption failure rates remain high, often surpassing 60%, due to factors such as poor usability, resistance to change, and the lack of a user-centered approach. The study concludes that success lies not just in technology adoption, but in its strategic integration, aligned with an organizational culture that prioritizes data analysis, user experience, and the building of long-term relationships, measured by Customer Lifetime Value (CLV). A proposed analysis model combines the Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT), and Task-Technology Fit (TTF) to guide future implementations and research in the sector.